Paleoindian occupation of the White Mountains, New Hampshire - Boisvert, Richard (Géographie physique et Quaternaire, 1999)
Abstract The earliest human occupation of the White Mountains region occurred approximately 11 000 14 C years ago. A suite of stylistically and technologically distinctive chipped stone tools have been found that correlate with similar artifacts and assemblages known across North America and identified as Paleoindian. This culture endured in the White Mountains for at least a millennium and coincided, at least in part, with the Younger Dryas climatic episode. Seven Paleoindian sites and their artifact assemblages are described. These sites appear to correlate with major river drainages and to articulate with widely separated Paleoindian sites outside the region. Key to the interpretation of these sites is the identification of the sources of the lithics used by the Paleoindians for their tools. Local rhyolite was acquired for use in two localities, Berlin and Jefferson, NH and chert from the Munsungun Lake region of northern Maine was imported. The movement of these lithics into and out of the White Mountains provides a perspective on inter-regional movement and contacts. The persistence and extent of the Paleoindian occupation of the White Mountains is a testimony to the highly successful adaptation to a harsh and variable climate, however the mechanisms of the subsistence and settlement patterns are poorly known. A broad outline of directions for future research is offered, with an emphasis on chronology and environmental reconstruction.